(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The experiment was conducted with a view to investigate the effect of urea molasses straw (UMS), urea treated straw (UTS) and silage in the diets on growth performance of goats in Subornochar upazilas of Noakhali district. Total DM intake was significantly (P<0.05) higher in silage fed group than UMS and UTS group. ME (MJ/d) intake was higher (P<0.05) in UMS (6.68) and silage (6.78) group than UTS (3.48) group. The mean values of live weight gains (g/d) were 44.11, 43.88 and 50.89 for UMS, UTS and silage, respectively which varied significantly (P<0.05) among the groups. There were no significant variation among the dietary groups of animals in case of DM, CP, ADF and OM digestibility. There were significant (P<0.05) differences among the mean values of nitrogen retention (%) , the silage (34%) group of animals showed significantly higher values than those of UMS (30.32%) and UTS (29.10%) group. Diets with silage resulted was better weight gain and nitrogen balance compared to UMS and UTS. So, introduction of silage may be practiced in the existing feeding system for increase the productivity of goats. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 95-99